2018
DOI: 10.14479/jkoos.2018.23.4.407
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Accommodative Response and Accommodative Lag Among Different Luminance of Near Visual Media

Abstract: This study was conducted to compare and analyze the effect of near visual media luminance on accommodative response (AR) and accommodative lag (AL) between emmetropia and myopia, and found out the near visual media to be caused burdensome on eyes in terms of AR and AL. Methods: Forty adult men and women (40 eyes) with ages averaging 22.57±2.07 years, who were not accommodative function disorder. 11 adults were emmetropes (average spheric equivalent power-0.34±0.22 D) and 29 adults were myopes (average spheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…[31][32][33] While it is expected that accommodative adaptation should be similar for both reading tasks, other factors such as differences in target luminance, pixel format and spatial frequency of the content could have led to a lower accommodative lag while reading text from a paper than the smartphone. 16,17 The findings of the current study are in general agreement with Mallen et al 34 where the changes in axial length under the influence of accommodation were shown to be dependent on the level of accommodative demand, with a significant increase in axial length being found only at a high accommodative stimulus of 6D (p = 0.02), and not at 2D (p = 0.27) or 4D (p = 0.08). In this study, we found that the magnitude of axial length change after different visual tasks was dependent on the properties of the near stimulus resulting in different levels of response, and hence a significant difference in axial length change across the visual tasks (p = 0.02).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…[31][32][33] While it is expected that accommodative adaptation should be similar for both reading tasks, other factors such as differences in target luminance, pixel format and spatial frequency of the content could have led to a lower accommodative lag while reading text from a paper than the smartphone. 16,17 The findings of the current study are in general agreement with Mallen et al 34 where the changes in axial length under the influence of accommodation were shown to be dependent on the level of accommodative demand, with a significant increase in axial length being found only at a high accommodative stimulus of 6D (p = 0.02), and not at 2D (p = 0.27) or 4D (p = 0.08). In this study, we found that the magnitude of axial length change after different visual tasks was dependent on the properties of the near stimulus resulting in different levels of response, and hence a significant difference in axial length change across the visual tasks (p = 0.02).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the previous literature, 15,16,19 this study found that the accommodative response varied with the type of near target. A higher lag of accommodation was observed when watching a video (≈0.90 D) compared with reading text from a smartphone (≈0.50 D) or on paper (≈0.25 D).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations